Investigation of the Synergistic Effect of Brown Sugar, Longan, Ginger, and Jujube (Brown Sugar Longan Ginger Tea) on Antioxidation and Anti-Inflammation in In Vitro Models. (2nd December 2020) - Lin, Ping; Kan, Kai-Wen; Chen, Jia-Haur; Lin, Yung-Kai; Lin, Yung-Hao; Lin, Yung-Hsiang; Hu, Wei-Chun; Chiang, Chi-Fu; Kuan, Chen-Meng
Abstract : This research unveils the synergistic effect of brown sugar, longan, ginger, and jujube on the beneficial effects of antioxidation and anti-inflammation. Longan, ginger, and jujube are ubiquitous herbs in traditional Chinese medicine (TCM) and are frequently used in folk remedies. Longan and ginger have been reported to be beneficial for antioxidation, anti-inflammation, ant-obesity, and nonalcoholic fatty liver disease (NAFLD) improvements. However, the potential scientific and medical benefits of their combination Brown Sugar Longan Ginger Tea (BSLGT), a popular drink in Chinese cultures, are elusive. Through the in vitro methodologies, we discovered that BSLGT could significantly improve the mitochondrial activity, antioxidant capacity, lipid content, and inflammatory response in human hepatocytes. In addition, BSLGT also exerted positive effects on the downregulation of atherosclerosis-associated, vasoconstrictor, and thrombosis-related gene expression in human umbilical vein endothelial cells. In short, our experimental results successfully revealed that the antioxidative and anti-inflammatory effects of BSLGT may have the potential to improve liver metabolism and cardiovascular inflammation although solid evidence requires further investigation.